(untitled) (JURNAL MAHATVAVIRYA, 2024)
Information technology continues to develop along with the changing times. In the military service, the benefits of information and communication technology are very pronounced, as seen in the daily tasks of the Army Information and Data Processing Service Personnel, where computers are their main tool. This research aims to analyze the influence of the development of information and communication technology on the implementation of TNI tasks. This research uses a qualitative method with a literature study approach. The results show that the development of information and communication technology (ICT) has a significant impact on the implementation of TNI tasks. However, in addition to the benefits, rapid technological progress also brings negative impacts, including deviations in behavior, ethics, norms, and morals due to unwise use. Thus, the positive impact of technology is highly dependent on how it is used